Desenvolvimento de nanocompósitos biodegradáveis de carragena e amido reforçados com nanocristais de celulose para embalagens de alimentos - Alves, João Marcelo de Lima (2025)
Food safety has become a significant focus of research efforts. Extending the shelf life of food not only benefits economic productivity but also prevents the consumption of food contaminated by microorganisms. Additionally, issues related to the use of plastic in the packaging industry have intensified the search for biodegradable and renewable materials. This study aimed to prepare and characterize edible nanocomposite films composed of carrageenan and arrowroot starch, reinforced with cellulose nanocrystals (CNC). Besides CNC, additives such as glycerol (as a plasticizer), aloe vera gel (to provide antibacterial properties), sesame oil (as an antioxidant), myristic acid (as a surfactant and compatibilizer), and hibiscus flower extract (as a pH indicator) were incorporated. In the produced films, the levels of additives were kept constant, while the compositions of the carrageenan/starch blends and the CNC content were varied. The composite films, prepared by dispersing the mixture's components in water at 80 °C, were evaluated using FTIR, SEM, water contact angle measurements, thickness, water vapor and oil permeability, UV-vis transmittance, moisture absorption, water solubility, TGA, DSC, and tensile tests. Based on SEM images, good dispersion of cellulose nanocrystals (CNC) was observed, and balanced proportions of starch and carrageenan resulted in more homogeneous structures. The films showed reasonable transparency in the visible region and low transmission in the UV region, making them promising for packaging with UV radiation barrier properties. Films with lower carrageenan content exhibited lower water vapor permeability and moisture absorption, regardless of CNC content, and oil permeability was nonexistent across all compositions. Moreover, higher starch content provided greater thermal stability to the films, and increased CNC content improved the mechanical properties of the composite films. Overall, the films demonstrated excellent biodegradability. The biodegradation tests revealed that the films degrade rapidly, with a mass loss exceeding 92% in 170 days. These results suggest that the developed films are promising for replacing conventional plastic packaging, contributing to the reduction of environmental impact.